CHARACTERIZATION AND MICROWAVE-ASSISTED HYDROLYSIS OF SAGO STARCH TO PRODUCE MALTODEXTRIN - Fajriutami, Triyani; Laksana, Raden Permana Budi; Hermiati, Euis (LIPI Press, 2014)
Sago (Metroxylon sagu Rottb.) starch is one of potential sources of starch in Indonesia; however, it has not been widely used as industrial raw material for modified starch, such as maltodextrin, which has higher addedvalue than the native sago starch. The aim of this study was to develop the processing technology of maltodextrin production from sago starch using microwave irradiation. The addition of activated carbon had a significant effect on the sugar produced in the microwave-assisted hydrolysis. The longer the duration of microwave irradiation the higher the total dissolved solids in the filtrate, and the lower the pH values. The increase of the microwave power level from 550 to 770 W significantly affected sugar content of the hydrolysates. Suitable Dextrose Equivalent (DE) value of maltodextrin (?20) can be obtained after hydrolysis for 10 to 12 minutes at the power level of 550 W or 6 to 8 minutes at the power level of 770 W.